KAJIAN POTENSI DAN KARAKTERISTIK TANAH BEKAS PENAMBANGAN SEBAGAI LAHAN SAWAH DI KECAMATAN PANGKALAN JAMBU KABUPATEN MERANGIN PROVINSI JAMBI - Dedy Antony; Weni Wilia; Agus Kurniawan Mastur (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
The phenomenon of people's gold mining or often called gold mining without permit (PETI) in Merangin Regency, Jambi Province is a serious problem because it occurs in productive paddy fields. This activity causes damage to paddy fields due to processes during mining activities. After the mining activity, the damaged paddy fields needed handling, especially for being reclaimed into paddy fields again. The research was conducted at the Baru Pangkalan Jambu Village, Pangkalan Jambu District, Merangin Regency, Jambi Province. The research took place from May to November 2022 which consisted of two stages, namely: 1) mapping the potential of ex-mining land to become rice fields, 2). Analysis of soil characteristics in paddy fields that have been reclaimed. Data were analyzed descriptively based on the criteria of soil physical and chemical properties based on PPT Bogor (1994). The results showed that the soil physical properties of paddy rice fields from reclamation of former mines had relatively low bulk density, coarse soil texture (sandy loam). The chemical properties of the soil indicate that the land has very low organic C and total nitrogen and a relatively acidic to slightly acidic soil pH. Research shows that the quality of this soil tends to increase with the duration of post-reclamation utilization.Keywords: Paddy field, land reclamation, unauthorized people's mining, land quality